Negative pressure wound therapy promotes healing and reduced pain in patients with acute suppurative mastitis - Lin Qiu; Feng Wang; Qin Xu; Zhenlv Lin; Bo Lin; Meng Huang; Qiaoyi Wu (BMC, 2022)
Abstract Background The purpose of this study was to compare the outcomes of vacuum sealing drainage (VSD) and conventional incision and drainage (I&D) for treating acute suppurative mastitis. Methods Hospital medical records were searched for patients 20-50 years of age who were diagnosed with acute suppurative mastitis from January 2014 to December 2018, and treated with traditional I&D or VSD. Patients were divided into those treated with VSD and I&D, and outcomes including pain, healing time, length of hospital stay, and length of antibiotic course were compared between the groups. Pain was evaluated with a numeric rating scale from 0 (no pain) to 10 (most severe pain). Subgroup analysis of lactating women was also performed. Results There were 110 women who received traditional I&D, and 105 women that received VSD included. The 2 groups were similar with respect to age (31.1 ± 4.8 vs. 29.9 ± 4.4, p = 0.058), and disease characteristics. The median pain score of women who received VSD (5 [IQR 5-6]) was significantly less than that of women who received I&D (8 [IQR 7-8]) (p < 0.001). The time for healing was significantly less in women who received VSD (40 days [IQR 30-45 days]) compared to I&D (60 days [IQR 45-70 days]) (p < 0.001). The length of hospital say and the length of antibiotic treatment were similar between the 2 groups. Results were similar for lactating women. Conclusions VSD is effective for treating acute suppurative mastitis with reduced pain and shortening healing time.